Effect of maternal and postweaning folic acid supplementation on global and gene‐specific DNA methylation in the liver of the rat offspring. Issue 4 (6th March 2013) - Sie, Karen K. Y.; Li, Jennifer; Ly, Anna; Sohn, Kyoung‐Jin; Croxford, Ruth; Kim, Young‐In; Ulrich, Cornelia M.; Miller, Joshua W.
<x xml:space="preserve">Abstract</x> Scope Intrauterine and early‐life exposure to folic acid has significantly increased in North America owing to folic acid fortification, widespread supplemental use, and periconceptional supplementation. We investigated the effect of maternal and postweaning folic acid supplementation on DNA methylation in the rat offspring. Methods and results Female rats were placed on a control or folic acid‐supplemented diet during pregnancy and lactation. At weaning, pups from each maternal diet group were randomized to the control or supplemented diet for 11 weeks. At weaning, maternal folic acid supplementation significantly decreased global (p < 0.001) and site‐specific DNA methylation of the Ppar‐γ, ER‐α, p53, and Apc genes (p < 0.05) in the liver. At 14 weeks of age, postweaning, but not maternal, folic acid supplementation significantly decreased global DNA methylation (p < 0.05). At 14 weeks of age, both maternal and postweaning folic acid supplementation significantly increased DNA methylation of the Ppar‐γ, p53, and p16 genes (p < 0.05) whereas only postweaning FA supplementation significantly increased DNA methylation of the ER‐α and Apc genes (p < 0.05). Conclusion Our data suggest that maternal and postweaning folic acid supplementation can significantly modulate global and gene‐specific DNA methylation in the rat offspring. The functional ramifications of the observed DNA methylation changes need to be determined in future studies.